2023
DOI: 10.1080/14786419.2023.2169687
|View full text |Cite
|
Sign up to set email alerts
|

New benzaldehyde derivatives from the fruiting bodies of Hericium erinaceus with cytotoxic activity

Abstract: New benzaldehyde derivatives from the fruiting bodies of Hericium erinaceus with cytotoxic activityFour new natural compounds named hericenone O (1), hericenone P (2), hericenone Q (3), and hericenone R (4), two of them were reported synthetically (3-4), together with eleven known compounds were isolated from the fruiting bodies of Hericium erinaceus. The chemical structures of the isolated compounds were elucidated by using NMR analysis and mass spectrometry, as well as comparisons with the reported data in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Anti-cancerous potential-against human colorectal carcinoma and liver cancer cell lines in vitro-Hep-G2 and HCT-116 cells [74] hericenone C and its deacylated derivative…”
Section: H Erinaceus Fruiting Bodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-cancerous potential-against human colorectal carcinoma and liver cancer cell lines in vitro-Hep-G2 and HCT-116 cells [74] hericenone C and its deacylated derivative…”
Section: H Erinaceus Fruiting Bodiesmentioning
confidence: 99%
“…In another analysis by Ruan et al, cytotoxic activity against cancer cells was tested using several benzaldehyde derivatives isolated from H. erinaceus . Hericenone Q showed moderate cytotoxic activity against a human colorectal carcinoma cell line (HCT-116) and a strong activity against a human liver cancer cell line (Hep-G2) [ 74 ]. A comparative investigation of the neuroprotective properties of H. erinaceus -isolated hericenone C and deacylhericenone (hericenone C treated with lipase), published by Shimizu, also demonstrated that the BDNF mRNA expression in human astrocytoma cells (1321N1) and the protection against H 2 O 2 -induced oxidative stress were considerably higher in the case of deacylhericenone [ 75 ].…”
Section: Identification Of Novel Bioactive Compounds In Her...mentioning
confidence: 99%
“…This mushroom species has long been used in traditional Chinese medicine, and is known to have positive effects in health, including neuroprotection, and improvements in the digestive, circulatory, and immune systems [1]. Over the years, many studies have been dedicated to identifying the bioactive compounds in H. erinaceus [2][3][4]. Hericerins, erinacines, erinacerins, erinaceolactones, glycoproteins, polysaccharides, sterols, and various volatile compounds are some groups of bioactive compounds isolated from their fruiting bodies and mycelia [5].…”
Section: Introductionmentioning
confidence: 99%